HUBUNGAN KETERAMPILAN MEMBACA APRESIATIF PUISI DENGAN KETERAMPILAN MENULIS PUISI SISWA KELAS X SMA NEGERI 2 PARIAMAN - Syafrizal, Pratiwi; Tamsin, Andria Catri; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2016)
ABSTRACTÂ This research to determine the following matters. First, describe the ability to read an appreciative poetry class X SMA 2 Pariaman. Second, describe the ability to write poetry class X SMA 2 Pariaman. Third, analyze the relationship between the ability to read an appreciative with the ability to write poetry class X SMA 2 Pariaman. Based on the results of the study, concluded the following three points. First, appreciative poetry reading skills class X SMA 2 Pariaman is located on more than enough qualifications (LDC) with the average value (70.38), while the skill of writing poetry class X SMA 2 Pariaman is also on the qualification of more than enough (LDC) with the average value (72.32). Third, based on the t-test, the alternative hypothesis (H1) is accepted at 95% confidence level and degrees of freedom n-1 for t> t table, namely 5.18> 1.68.Â Kata Kunci: hubungan, membaca apresiatif, puisi